Assessment of Image Quality in Real Time Three-Dimensional Dobutamine Stress Echocardiography: An Integrated 2D/3D Approach. - Johri, Amer M.; Chitty, David W.; Hua, Lanqi; Marincheva, Gergana; Picard, Michael H. (Echocardiography, 2015)
Background Three-dimensional (3D) stress echocardiography is a relatively new technique offering the potential to acquire images of the entire left ventricle from 1 or 2 transducer positions in a time-efficient manner. Relative to two-dimensional (2D) imaging, the ability to quickly acquire full volume images during peak stress with 3D echocardiography can eliminate left ventricular ( LV) foreshortening while reducing inter-operator variability. Our objectives were to (1) determine the practicality of a novel integrated 2D/3D stress protocol in incorporating 3D imaging into a standard 2D stress echocardiogram and (2) to determine whether the quality of imaging using the novel 2D/3D protocol was sufficient for interpretation. Methods Twenty-five patients referred for stress echocardiography underwent an integrated 2D/3D image acquisition protocol. LV segments were scored from 0 (absent or no clear endocardial visualization) to 3 (excellent/full visualization of endocardial border) with each modality. 2D segment quality scoring was compared with 3D. An integrated score was compared with either 2D or 3D imaging alone. Results Two-dimensional and 3D imaging were optimal for differing segments and the integrated protocol was superior to either modality alone. 3D imaging was superior in visualizing the anterior and anterolateral region of the base segments, compared to 2D imaging. 3D imaging was less useful for the base, the mid-inferior, and the inferoseptal segments, thus emphasizing the need to retain 2D imaging in stress echocardiography at this time. Conclusion The integrated 2D/3D protocol approach to stress echocardiography is technically feasible and maximizes image quality of dobutamine stress echocardiography, improving patient assessment.